La cultura del suburbio y las nuevas alternativas de diseño urbano en EE.UU. - Mawromatis P., Constantino (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 1995)
The American urban and suburban landscape has been deteriorating over the last decades. Urban process has been directed mainly by economic and speculative forces. The population, hence has been treated as a market, in a scenario in wich standardization and assembly line production maximized profit and minimized risks. As a result, the urban space lost its richness and its identity, thus weakening the sense of community Nowadays, much of the American population lives in an alienating environment, where distrust, aggressiveness and frustration underminetheir existence. To revert this destructive tendency we have to understand the city as a complex mélange of social, political, economical and cultural phenomena interacting in a physical space. Urban design ought to constitute the instrument to shape the public realm and the urban form. Currently, and as a consequence of the crisis in modern cities, urban design as a discipline is gaining momentum. Today, new emerging alternatives are considered viable contributions to enhance our manmade environment.